Murine cd4+ T cell Responses are inhibited by cytotoxic T cell-mediated killing of dendritic cells and are restored by antigen transfer - Ma, Joel Zhi-Iong (2013)
Cytotoxic T lymphocytes (CTL) provide protection against pathogens and tumors. In addition, experiments in mouse models have shown that CTL can also kill antigen-presenting dendritic cells (DC), reducing their ability to activate primary and secondary CD8+ T cell responses. In contrast, the effects of CTL-mediated killing on CD4+ T cell responses have not been fully investigated. Here we use adoptive transfer of TCR transgenic T cells and DC immunization to show that specific CTL significantly inhibited CD4+ T cell proliferation induced by DC loaded with peptide or low concentrations of protein antigen. In contrast, CTL had little effect on CD4+ T cell proliferation induced by DC loaded with high protein concentrations or expressing antigen endogenously, even if these DC were efficiently killed and failed to accumulate in the lymph node (LN). Residual CD4+ T cell proliferation was due to the transfer of antigen from carrier DC to host APC, and predominantly involved skin DC populations. Importantly, the proliferating CD4+ T cells also developed into IFN-γ producing memory cells, a property normally requiring direct presentation by activated DC. Thus, CTL-mediated DC killing can inhibit CD4+ T cell proliferation, with the extent of inhibition being determined by the form and amount of antigen used to load DC. In the presence of high antigen concentrations, antigen transfer to host DC enables the generation of CD4+ T cell responses regardless of DC killing, and suggests mechanisms whereby CD4+ T cell responses can be amplified.